2014
DOI: 10.1080/03057240.2013.866940
|View full text |Cite
|
Sign up to set email alerts
|

Good and evil at school: Bullying and moral evaluation in early adolescence

Abstract: We investigated how adolescents (sixth-graders, N = 357) morally evaluated hypothetical bullying and defending protagonists and whether these evaluations related to behavior in bullying as nominated by peers. Exploratory factor analysis (EFA) resulted in four factors for the evaluation of the hypothetical bullies: Evil soul, Contempt, Cowardice, and Deviance, and five factors for the evaluation of the hypothetical defender: General admiration, Courage, Cool, Empathic care, and Fair justice. Corresponding scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Finally, it is possible that students who defend others in accordance with their moral motivation become more socially preferred. Early adolescents appreciate defending in terms of admirable, courageous, cool, caring and fair behaviour (Kollerová et al, 2014). We lack longitudinal studies that could shed light on these issues, but from a theoretical perspective, high peer status may not only be an antecendent to, but also a consequence of, defending (Salmivalli, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that students who defend others in accordance with their moral motivation become more socially preferred. Early adolescents appreciate defending in terms of admirable, courageous, cool, caring and fair behaviour (Kollerová et al, 2014). We lack longitudinal studies that could shed light on these issues, but from a theoretical perspective, high peer status may not only be an antecendent to, but also a consequence of, defending (Salmivalli, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Even though students themselves appreciate various positive features of defending (Kollerová et al 2014), the decision to defend someone is far from straightforward because it involves a social risk (Pöyhönen et al 2010). By taking the side of a victimized peer, students may risk their status in the peer group and even put themselves at risk of becoming a target of aggression (Huitsing et al 2014).…”
Section: Prerequisites Of Defendingmentioning
confidence: 99%
“…Here, studies with children have revealed that bystanders who adopt a more active role as defenders of those being cyberbullied showed higher levels of moral sensitivity and emotional contagion, as well as high self-efficacy (Gini, 2006; Pöyhönen, Juvonen, & Salmivalli, 2010; Vannini et al, 2011). Other studies, however, have not succeeded in identifying cognition measures that predict defender behavior (Andreou & Metallidou, 2004; Correia & Dalbert, 2008; Kollerová, Janošová, & Říčan, 2014), although girls seem to adopt the roles of defender and outsider more frequently than boys (Salmivalli, Lagerspetz, Björkqvist, Österman, & Kaukiainen, 1996).…”
Section: Introductionmentioning
confidence: 98%